2021
DOI: 10.1155/2021/9974890
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Signal‐Modulating Effects of Brown Seaweed‐Derived Compounds against Oxidative Stress‐Associated Pathology

Abstract: The biological and therapeutic properties of seaweeds have already been well known. Several studies showed that among the various natural marine sources of antioxidants, seaweeds have become a potential source of antioxidants because of their bioactive compounds. Most of the metabolic diseases are caused by oxidative stress. It is very well known that antioxidants have a pivotal role in the treatment of those diseases. Recent researches have revealed the potential activity of seaweeds as complementary medicine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 184 publications
(269 reference statements)
1
26
0
Order By: Relevance
“…In that study, the concentration of β-carotene ( A ) did not alter intracellular levels of ROS but rather downregulated the essential antioxidant enzymes that maintain redox homeostasis in cancer cells. This result confirms that β-carotene ( A ) can modify t the intracellular antioxidant status [ 40 ]. Therefore, the negative regulation of these enzymes was vital in the induction of apoptosis by the mitochondrial pathway.…”
Section: Pro-apoptotic Activity Of Bioactive Compounds From Seaweedssupporting
confidence: 76%
See 2 more Smart Citations
“…In that study, the concentration of β-carotene ( A ) did not alter intracellular levels of ROS but rather downregulated the essential antioxidant enzymes that maintain redox homeostasis in cancer cells. This result confirms that β-carotene ( A ) can modify t the intracellular antioxidant status [ 40 ]. Therefore, the negative regulation of these enzymes was vital in the induction of apoptosis by the mitochondrial pathway.…”
Section: Pro-apoptotic Activity Of Bioactive Compounds From Seaweedssupporting
confidence: 76%
“…However, under abnormal physiological conditions, endogenous antioxidants like glutathione or antioxidant defense enzymes (SOD: superoxide dismutase; CAT: catalase; GPx: glutathione peroxidase), although highly efficient, cannot protect the cell from the effects of ROS. Antioxidants play a vital role in cancer by counteracting the activity of ROS [ 40 ].…”
Section: Apoptosis: a Target For Anticancer Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…The consumption of microgreens can prevent or alleviate some health problems including inflammation of the immune system pathways, obesity (Castelão-Baptista et al ., 2021), cardiovascular disease, type 2 diabetes, cancers and modulation of the gut microbiome (Machlin and Bendich, 1987). Other studies have reported that their abundance in vitamins C, E, K, carotenoids and polyphenols, has the potential to regulate cellular pathways, modulating inflammation (Choe et al ., 2018; Begum et al ., 2021; Sirajunnisa et al ., 2021), as well as the generation and scavenging of reactive oxygen species (Finley et al ., 2011).…”
Section: Health Benefits Of Microgreensmentioning
confidence: 99%
“…The autoclaved-dried aqueous extract had lower NBT value compared to shadow-dried and the control group. In a study it is proved that the seaweed is rich in antioxidant properties, thus it creates a protective barrier against the oxidative stress (Begum, R., et al, 2021) 13 . Therefore, in this research it can be concluded that seaweed contain some antioxidant properties due to which free-radicals were less in the treatment group.…”
Section: Table 1: Different Feeding Group and Hemoglobin Level In Chi...mentioning
confidence: 99%